Biomechanical Evaluation of the Lumbar Spine by Using a New Interspinous Process Device: A Finite Element Analysis - Hung-Wen Wei (MDPI AG, 2021)
Minimally invasive decompression is generally employed for treating lumbar spinal stenosis; however, it results in weakened spinal stability. To augment spinal stability, a new interspinous process device (NIPD) was developed in this study. The biomechanical features of the NIPD were evaluated in this study. Three finite-element (FE) models of the entire lumbar spine were implemented to perform biomechanical analysis: the intact, defect (DEF), and NIPD models. The DEF model was considered for lumbar spines with bilateral laminotomies and partial discectomy at L3–L4. Range of motion (ROM), disc stress, and facet joint contact force were evaluated in flexion, extension, torsion, and lateral bending in the three FE models. The results indicated that ROM in the extension increased by 23% in the DEF model but decreased by 23% in the NIPD model. In the NIPD model, the cephalic adjacent disc stress in flexion and extension was within 5%, and negligible changes were noted in the facet joint contact force for torsion and lateral bending. Thus, the NIPD offers superior spinal stability and causes only a minor change in cephalic adjacent disc stress in flexion and extension during the bilateral laminotomy and partial discectomy of the lumbar spine. However, the NIPD has a minor influence on the ROM and facet joint force for lateral bending and torsion.